Experimental and numerical studies on post-fire behaviour of S700 high strength steel circular hollow sections under combined compression and bending - Zhong, Yukai (2022)
The present paper reports experimental and numerical investigations into the post-fire local buckling behaviour and residual resistances of S700 high strength steel circular hollow sections (CHS) under combined compression and bending. A testing programme was firstly conducted and included heating and cooling of specimens as well as post-fire material tensile coupon tests and eccentrically loaded stub column tests. Following the testing programme, a numerical modelling programme was carried out, where finite element models were developed to replicate the test results and then employed to perform parametric studies to generate further numerical data over a wide range of cross-section dimensions and loading combinations. Due to the absence of design standards for high strength steel structures after exposure to fire, the codified ambient temperature design interaction curves for high strength steel CHS under combined compression and bending were assessed, using post-fire material properties, for their applicability to post-fire S700 high strength steel CHS. The assessment results revealed that the design interaction curves in the European code and American specification yield a satisfactory level of accuracy and consistency when used for post-fire S700 high strength steel CHS, while the design interaction curves in the Australian standard provide slightly conservative residual resistance predictions.